Abalone visceral extract inhibit tumor growth and metastasis by modulating Cox-2 levels and CD8+ T cell activity - II Kim Jae; Im Chang-Rok; Kang Sung; Ryu Jae; Kwon Ho-Keun; Lee Choong-Gu; Im Sin-Hyeog (BMC, 2010)
Abstract Background Abalone has long been used as a valuable food source in East Asian countries. Although the nutritional importance of abalone has been reported through in vitro and in vivo studies, there is little evidence about the potential anti-tumor effects of abalone visceral extract. The aim of the present study is to examine anti-tumor efficacy of abalone visceral extract and to elucidate its working mechanism. Methods In the present study, we used breast cancer model using BALB/c mouse-derived 4T1 mammary carcinoma and investigated the effect of abalone visceral extract on tumor development. Inhibitory effect against tumor metastasis was assessed by histopathology of lungs. Cox-2 productions by primary and secondary tumor were measured by real-time RT-PCR and immunoblotting (IB). Proliferation assay based on [3H]-thymidine incorporation and measurement of cytokines and effector molecules by RT-PCR were used to confirm tumor suppression efficacy of abalone visceral extract by modulating cytolytic CD8+ T cells. The cytotoxicity of CD8+ T cell was compared by JAM test. Results Oral administration of abalone visceral extract reduced tumor growth (tumor volume and weight) and showed reduced metastasis as confirmed by decreased level of splenomegaly (spleen size and weight) and histological analysis of the lung metastasis (gross analysis and histological staining). Reduced expression of Cox-2 (mRNA and protein) from primary tumor and metastasized lung was also detected. In addition, treatment of abalone visceral extract increased anti-tumor activities of CD8+ T cells by increasing the proliferation capacity and their cytolytic activity. Conclusions Our results suggest that abalone visceral extract has anti-tumor effects by suppressing tumor growth and lung metastasis through decreasing Cox-2 expression level as well as promoting proliferation and cytolytic function of CD8+ T cells.